Chemotherapy induces stemness in osteosarcoma cells through activation of Wnt/β-catenin signaling. Issue 2 (28th January 2016) - Martins-Neves, Sara R.; Paiva-Oliveira, Daniela I.; Wijers-Koster, Pauline M.; Abrunhosa, Antero J.; Fontes-Ribeiro, Carlos; Bovée, Judith V.M.G.; Cleton-Jansen, Anne-Marie; Gomes, Célia M.F.
Highlights: Chemotherapy induces a phenotypic stem-like cell transition in osteosarcoma. Conventional drugs increase ALDH activity and ABC transporters expression. Doxorubicin upregulates stemness markers by activation of Wnt/β-catenin. Wnt/β-catenin inhibition prevents doxorubicin-induced stem-like phenotype. Stemness-related markers correlate with worst survival in osteosarcoma patients. Abstract: Development of resistance represents a major drawback in osteosarcoma treatment, despite improvements in overall survival. Treatment failure and tumor progression have been attributed to pre-existing drug-resistant clones commonly assigned to a cancer stem-like phenotype. Evidence suggests that non stem-like cells, when submitted to certain microenvironmental stimuli, can acquire a stemness phenotype thereby strengthening their capacity to handle with stressful conditions. Here, using osteosarcoma cell lines and a mouse xenograft model, we show that exposure to conventional chemotherapeutics induces a phenotypic cell transition toward a stem-like phenotype. This associates with activation of Wnt/β-catenin signaling, up-regulation of pluripotency factors and detoxification systems (ABC transporters and Aldefluor activity) that ultimately leads to chemotherapy failure. Wnt/β-catenin inhibition combined with doxorubicin, in the MNNG-HOS cells, prevented the up-regulation of factors linked to transition into a stem-like state and can be envisaged as a way to overcome adaptive resistance. Finally, the analysis of the public R2 database, containing microarray data information from diverse osteosarcoma tissues, revealed a correlation between expression of stemness markers and a worse response to chemotherapy, which provides evidence for drug-induced phenotypic stem cell state transitions in osteosarcoma.